Deployment of attention to facial expressions varies as a function of emotional quality—but not in alexithymic individuals - Surber, Chiara; Hoepfel, Dennis; Günther, Vivien; Kersting, Anette; Rufer, Michael; Suslow, Thomas; Bodenschatz, Charlott Maria (Frontiers in Psychiatry, 2024)
Background Alexithymia is a risk factor for emotional disorders and is characterized by differences in automatic and controlled emotion processing. The multi-stimulus free-viewing task has been used to detect increased negative and reduced positive attentional biases in depression and anxiety. In the present eye-tracking study, we examined whether lexical emotional priming directs attention toward emotion-congruent facial expressions and whether alexithymia is related to impairments in lexical priming and spontaneous attention deployment during multiple face perception. Materials and methods A free-viewing task with happy, fearful, angry, and neutral faces shown simultaneously was administered to 32 alexithymic and 46 non-alexithymic individuals along with measures of negative affect and intelligence. Face presentation was preceded by masked emotion words. Indices of initial orienting and maintenance of attention were analyzed as a function of prime or target category and study group. Results Time to first fixation was not affected by prime category or study group. Analysis of fixation duration yielded a three-way interaction. Alexithymic individuals exhibited no prime or target category effect, whereas non-alexithymic individuals showed a main effect of target condition, fixating happy faces longer than neutral and angry faces and fearful faces longer than angry faces. Discussion Our results show evidence of attentional biases for positive and fearful social information in non-alexithymic individuals, but not in alexithymic individuals. The lack of spontaneous attentional preference for these social stimuli in alexithymia might contribute to a vulnerability for developing emotional disorders. Our data also suggest that briefly presented emotion words may not facilitate gaze orientation toward emotion-congruent stimuli.